The Effectiveness of Lullaby Music Therapy on Cough Intensity in Toddlers with ARI - Mutarobin Mutarobin; Mukhamad Muqtafin; Suryani Manurung (Poltekkes Kemenkes Palu, 2023)
ARI cases in the Banten area were 48,621 (53%). The age group that is most at risk of developing ARI is children under five (1-4 years) at 8.0%. The purpose of this study was to see the effectiveness of music therapy in reducing cough intensity. Quasi-experimental research method with pretest-posttest with the control group. The study sample consisted of 36 respondents (intervention and control groups). Inclusion criteria were patients with ARI, toddlers and preschoolers. place of research in the Banten regional hospital. Instruments are a scale for scoring cough and music Lullabies. Intervention and observation for the control group were carried out for 30 minutes 3 times with a pre and post-test. The analysis was carried out by frequency test and correlation test. Pre and post-cough intensity scores were analyzed using the dependent t-test. The results showed that Lullaby music therapy was effective on the cough intensity of children under five with ISPA (p<.05). Music therapy with complete administration has an effect on cough intensity (P<.05). Conclusion, music therapy is effective in reducing the cough intensity of toddlers with ARI.